Blog and intercultural grouping effect on learners' perceptions of intercultural communication projects - Awada, Ghada (2018)
This study investigated the effect of integrating Blog Assisted Language Learning(BALL) and small culturally -mixed group work on improving the perceptions of intercultural communication and writing research projects of university students (n=102) of different cultures enrolled in Advanced Rhetoric classrooms in two American universities during a 16-week period. The study employed Pre-test/Post-test control group design whereby the experimental group participants received the treatment encompassing the integration of blog-mediated instruction and culturally mixed group work and the control group received regular research instruction. Data were collected using two surveys. The findings proved that the treatment was effective in improving the experimental group perceptions of the intercultural communication and writing research projects whereas the control group did not show similar improvement.